Effectiveness of video-assisted teaching on knowledge regarding road traffic rules among college students, Puducherry - Chakali, Usha; Ramesh, Ronur S.; Olickal, Jeby J.; Surendran, Gayathri; Jayaseelan, Venkatachalam (International Journal Of Community Medicine And Public Health, 2020)
Background: Road traffic accidents are considered a public health problem leading to high mortality and morbidity, especially among adolescents and young adults. We aimed to assess the effectiveness of video-assisted teaching to improve the knowledge of road traffic rules among college students and the factors associated with the difference in knowledge. Methods: We conducted pre-test post-test study among students from a Government Arts and Science college in Puducherry, South India from August to September 2019. We assessed the knowledge related to road traffic rules like road traffic signs, speed limits and penalties related to violation of traffic rules. A video-assisted health education session was provided to all, and change in knowledge assessed. Factors associated with the difference in scores were assessed using an independent t-test or ANOVA test. Results: A total of 355 college students were included in the study. Of them, 2 (0.56%) had adequate knowledge, 317 (89.3%) had moderate knowledge and 36 (10.14%) had inadequate knowledge regarding traffic rules in the pre-test. During post-test, 47 (13.24%) had moderate knowledge and 308 (86.7%) had adequate knowledge. Overall mean (SD) knowledge score was increased from 14.7 (2.8) to 23.6 (2.5) (p<0.001). Sociodemographic factors were not significantly associated with a change in knowledge scores. Conclusions: There was a significant difference in knowledge scores of students after the intervention. Continuous reinforcement and education about safety measures can motivate and bring a positive change among them in strictly following traffic rules.